2021
DOI: 10.46984/sebatik.v25i1.1279
|View full text |Cite
|
Sign up to set email alerts
|

Dinamika Sistem Ekonomi Sirkular Berbasis Masyarakat Metode Causal Loop Diagram Kota Bengkayang

Abstract: Ekonomi sirkular merupakan sebuah konsep ekonomi yang mengimplementasikan tujuan pembangunan berkelanjutan yang terkait dengan tingkat konsumsi dan produksi yang bertanggung jawab dan berkelanjutan. Konsep ekonomi ini memberikan sebuah solusi dari permasalahan sampah yang diproduksi oleh masyarakat, dengan tujuan membuat produk baru dari sumber daya sampah yang bermanfaat dan bernilai ekonomi. Tujuan penelitian ini adalah mengidentifikasi permasalahan tata kelola sampah dalam kontribusinya terhadap perekonomia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
(18 reference statements)
0
7
0
10
Order By: Relevance
“…Circular economy is a concept that implements sustainable development goals related to responsible and sustainable levels of consumption and production. [16] Waste selection can be done independently and participatively in a community. In this case, it is necessary to increase the role of women as initiators in society.…”
Section: Results and Discussion 1 Policy And Use Of Mask Wastementioning
confidence: 99%
“…Circular economy is a concept that implements sustainable development goals related to responsible and sustainable levels of consumption and production. [16] Waste selection can be done independently and participatively in a community. In this case, it is necessary to increase the role of women as initiators in society.…”
Section: Results and Discussion 1 Policy And Use Of Mask Wastementioning
confidence: 99%
“…Peluang sirkularitas menjadi upaya untuk optimalnya manfaat bersama antara sosial, ekonomi dan lingkungan (PPN/Bappenas et al, 2021). Salah satu implementasi model ekonomi sirkular adalah melalui program bank sampah, dimana ada pengelolaan sampah (reduce, reuse, recycle) dan menjadi nilai ekonomi sehingga masyarakat mendapatkan keuntungan dari aspek pendapatan maupun lingkungan yang bersih (Dwiningsih & Harahap, 2022;Kristianto & Nadapdap, 2021;Purwanti, 2021).…”
Section: Pendahuluan *unclassified
“…The findings of empirical research have demonstrated that quality of the environment and public health will be affected if the amount of waste continues to grow unchecked and is not appropriately managed [7]. In other words, ineffective and inefficient waste management that does not employ environmentally friendly waste management methods and technology has a negative influence on population health and can contaminate the environment [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, local governments must determine preventive steps to reduce the occurrence of negative externalities, such as providing education, help, and socialization concerning the concept of reducing, reusing, and recycling [15] because development that takes into account the factors of environmental quality will promote the community's and the environment's well-being in a manner that is inclusive for both [16]. By implementing a circular economy, the amount of unprocessed trash generated at the household level can be effectively managed [7], [17].…”
Section: Introductionmentioning
confidence: 99%